Borrowed agricultural and economical terms adaptation specific to the category of gender (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the problem of peculiarities of adaptation of agricultural and economic borrowing terms to the category of gender. It is prescribed that they automatically acquire gender characteristics in Ukrainian language and formally in phonetic. The author proved an examples of analyzed terms that there isn't compliance in expression of category of gender in language-recipient and language-donor.
Keywords: borrowing term; language-recipient and language-donor